Efficacy and safety of nebivolol in Korean patients with hypertension by age and sex: a subanalysis from the BENEFIT-KOREA study - Kyoung Im Cho; Dong Woon Jeon; Hyo Seung Ahn; Dong Kyu Jin; Hyun Sang Lee; Jong-Young Lee; Hong-Seok Lim; Athanasios J. Manolis; Seung-Woon Rha; Sang Won Park (BMC, 2021)
Abstract Background BENEFIT-KOREA (BEnefits after 24 weeks of NEbivolol administration For essential hypertensIon patients wiTh various comorbidities and treatment environments in Korea) study, an observational study in South Korea, demonstrated the efficacy and safety of nebivolol in Asian patients with essential hypertension with and without comorbidities in real-world settings. We present a subanalysis of the efficacy and safety of nebivolol across age and sex in the BENEFIT-KOREA cohort. Methods Adult South Korean patients with essential hypertension participated in the prospective, single-arm, open, observational BENEFIT-KOREA study; 3011 patients received nebivolol as monotherapy or add-on therapy. Changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP), and pulse rate at 12 and 24 weeks were evaluated. Participants were divided into three age groups-young males and females: < 50 years; middle-aged males and females: ≥50 years to < 70 years; and older males and females: ≥70 years. Results The mean age of study participants was 63.5 ± 12.9 years; majority were between 50 and 69 years of age and 40.4% were females. A significant decrease was observed in mean SBP, DBP, and pulse rate from baseline at 12 and 24 weeks in males and females across all age groups analyzed (all P < 0.001 vs. baseline), with no significant difference in mean reduction in SBP and DBP from baseline between sex within the age groups. Majority of reported adverse events were mild. The incidence of adverse events was lower in young participants versus middle-aged and older participants. Conclusions Our subanalysis from the real-world BENEFIT-KOREA study in Asian patients with essential hypertension demonstrated the efficacy and safety of once-daily nebivolol across age groups with no between-sex differences. Trial registration Name of the registry: clinicaltrials.gov. Trial registration number: NCT03847350 . Date of registration: February 20, 2019 retrospectively registered.